Analysis the Surface Morphology of the Porous Media by using Atomic Force Microscope technique - Al-Zaidi, Bashir Y. Sherhan (Al-Khwarizmi Engineering Journal, 2018)
An atomic force microscope (AFM) technique is utilized to investigate the polystyrene (PS) impact upon the morphological properties of the outer as well as inner surface of poly vinyl chloride (PVC) porous fibers. Noticeable a new shape of the nodules at the outer and inner surfaces, namely "Crater nodules", has been observed. The fibers surface images have seen to be regular nodular texture at the skin of the inner and outer surfaces at low PS content. At PS content of 6 wt.%, the nodules structure was varied from Crater shape to stripe. While with increasing of PS content, the pore density reduces as a result of increasing the size of the pore at the fiber surface. Moreover, the test of 3D-AFM images shows that the roughness of both surfaces of fibers seems to be decreased with PS content. Alternatively, the fibers pure water permeability (PWP) has been declined with decreasing of fiber roughness.